Self-management Strategies of Music Teacher in Musical Interpretation Teaching - Ayu Niza Machfauzia (IJCAS (International Journal of Creative and Arts Studies), 2014)
In this paper, presented the results of a qualitative study of case studies of self- management strategies music teachers in interpretation of music teaching. The purpose of this research is to reveal the self-management strategies that teachers use in interpretation of music teaching. Subjects in this study were teachers who teach musical instrument practice as many as 12 people. In this study subject determined by purposive sampling technique. Interviews, observation, and documentation techniques are used for data collection. The data have been collected from being validated by using triangulation techniques and triangulation time, and analyzed by means of data reduction, data presentation, and inference data. The results showed that components of self-management strategies used by teachers which include motivation, teaching method,and monitoring performance.